The Contribution of Flexible Design in Prevention/Reduction of C&D Waste: An Educational Building Example in Kayseri - Salgin, Burcu; Tuna Taygun, Gokce; Balanli, Ayse (YILDIZ TECHNICAL UNIV, FAC ARCHITECTURE, 2018)
Throughout the functional lifetime of a building (in situations where the need, user, function, regulations or likes change), what is expected of an architectural design is its ability to adapt to change. Adaptability to change is possible with the flexibility approach. While flexible design allows change, it is also beneficial for preventing/reducing C&D waste. Because the building can be adapted to new circumstances without demolishing it completely or partially, it is possible to use the building products effectively and in such a way C&D waste can be prevented/reduced. In this research, an analysis is performed on the benefits of a flexible design in the prevention/reduction of C&D waste for a multi-functional, leased building whose function and user have not been defined: With this aim, a literature review was conducted on how a flexible design contributes to C&D waste prevention/reduction. Next, the flexible design steps for preventing/reducing the C&D wastes that are generated by changes/transformations/renewals during the usage phase of the building were put forward. A building located in Kayseri, which was designed in 2007 with the aim of flexibility, without user and function definition and has been used as an educational building since 2013, was examined. Specifically, the contribution of design flexibility on the prevention/reduction of the C&D waste generated during the usage phase of the building was examined, and the results were presented. The findings of the study show that the building had enough flexibility for its current use and future possible functions, and therefore, it was concluded that flexible design would be effective in the prevention/reduction of the C&D waste to be generated in case of changes.
Keywords: Flexible design; C&D waste; C&D waste prevention/reduction; Architecture